Bagaimana Anak Usia Dini Belajar Matematika? Suatu Tinjauan Literatur Konstruktivisme - Santa Murni A Situmorang; Srinahyanti Srinahyanti; Isa Hidayati (HIBRUL ULAMA, 2025)
The results of the PISA study, conducted over two decades, show that students' mathematical abilities in Indonesia are still far from standard. Mathematics education in Indonesia needs to accelerate improvements in the learning process to make it more meaningful, and this effort is based on early childhood education. Constructivists believe that the best way for children to learn mathematics is by doing mathematics themselves. Piaget, Vygotsky, and Bruner all believe that mathematical thinking skills in early childhood develop in line with and are integrated with other aspects of development, especially cognitive development. Learning is a process of constructing knowledge through direct experience and interaction with the environment, so learning is how to make sense of what they learn. Constructivist ideas recommend active, child-centered learning, and are related to discovering the meaning of what children experience. Exploratory, manipulative, cooperative, and discovery experiences provide opportunities for children to organize their cognitive structures and make their own discoveries in understanding concepts, reasoning, and solving mathematical problems.